2015
DOI: 10.1186/s40689-014-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermoset composites reinforced with recycled cotton textile residues

Abstract: The recycling of textiles is an issue that requires immediate attention in order to address the management of textiles derived from household waste, as well as scraps generated throughout manufacturing textile processes. The present study aimed to produce composites employing three different types of thermoset resins (epoxy, polyester orthophthalic and polyurethane) reinforced with recycled cotton textile residues on which tensile tests were carried out. The incorporation of 30% (v/v) of textile reinforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…An overview of the tensile modulus and strength of the ACCs compared to the results of other studies is shown in Fig. 5 [4,10,15,20,[29][30][31]. In brief, the tensile strength for the obtained ACCs in this study ranged from 25 to 29 MPa with an E-modulus from 2.5 to 4.3 GPa which were considerably higher than the values of ACCs reinforced by cotton being reported by Shibata et al [20].…”
Section: Mechanical Properties Of Acc Laminatesmentioning
confidence: 41%
See 3 more Smart Citations
“…An overview of the tensile modulus and strength of the ACCs compared to the results of other studies is shown in Fig. 5 [4,10,15,20,[29][30][31]. In brief, the tensile strength for the obtained ACCs in this study ranged from 25 to 29 MPa with an E-modulus from 2.5 to 4.3 GPa which were considerably higher than the values of ACCs reinforced by cotton being reported by Shibata et al [20].…”
Section: Mechanical Properties Of Acc Laminatesmentioning
confidence: 41%
“…The linen fabrics were processed to separate the polyester and cotton fibres by a first treatment with 10 N H 2 SO 4 , which was followed by a subsequent mechanical treatment. A detailed description of the process is found elsewhere [11]. The treatment gave a heterogeneous mixture consisting of a cotton suspension and solid polyester fibres.…”
Section: Cotton Separation From Polycotton Linen Fabricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, natural fiber composites currently represent one of the emerging areas in polymer science and technology for various end-use applications [7].…”
Section: Introductionmentioning
confidence: 99%